Integrating postabortion care, menstrual regulation and family planning services in Bangladesh: a pre-post evaluation - Biswas, Kamal K. (Reprod Health, 2017)
BACKGROUND: In Bangladesh, abortion is restricted except to save the life of a woman, but menstrual regulation is allowed to induce menstruation and return to non-pregnancy after a missed period. MR services are typically provided through the Directorate General of Family Planning, while postabortion care services for incomplete abortion are provided by facilities under the Directorate General of Health Services. The bifurcated health system results in reduced quality of care, particularly for postabortion care patients whose procedures are often performed using sub-optimal uterine evacuation technology and typically do not receive postabortion contraceptive services. This study evaluated the success of a pilot project that aimed to integrate menstrual regulation, postabortion care and family planning services across six Directorate General of Health Services and Directorate General of Family Planning facilities by training providers on woman-centered abortion care and adding family planning services at sites offering postabortion care. METHODS: A pre-post evaluation was conducted in the six large intervention facilities. Structured client exit interviews were administered to all uterine evacuation clients presenting in the 2-week data collection period for each facility at baseline (n = 105; December 2011–January 2012) and endline (n = 107; February–March 2013). Primary outcomes included service integration indicators such as provision of menstrual regulation, postabortion care and family planning services in both facility types, and quality of care indicators such as provision of pain management, provider communication and women’s satisfaction with the services received. Outcomes were compared between baseline and endline for Directorate General of Family Planning and Directorate General of Health Services facilities, and chi-square tests and t-tests were used to test for differences between baseline and endline. RESULTS: At the end of the project there was an increase in menstrual regulation service provision in Directorate General of Health Services facilities, from none at baseline to 44.1% of uterine evacuation services at endline (p < 0.001). The proportion of women accepting a postabortion contraceptive method increased from 14.3% at baseline to 69.2% at endline in Directorate General of Health Services facilities (p = 0.006). Provider communication and women’s rating of the care they received increased significantly in both Directorate General of Health Services and Directorate General of Family Planning facilities. CONCLUSIONS: Integration of menstrual regulation, postabortion care and family planning services is feasible in Bangladesh over a relatively short period of time. The intervention’s focus on woman-centered abortion care also improved quality of care. This model can be scaled up through the public health system to ensure women’s access to safe uterine evacuation services across all facility types in Bangladesh.